Self-assembled carbon nitride/cobalt (III) porphyrin photocatalyst for mimicking natural photosynthesis - Singh, Chandani; Chaubey, Surabhi; Singh, Pooja; Sharma, Kavita; Shambhavi; Kumar, Abhishek; Yadav, Rajesh K.; Dwivedi, D.K.; Baeg, Jin-Ook; Kumar, Utkarsh; Yadav, B.C.; Pandey, Gajanan (Diamond and related materials, 2020)
Natural photosynthesis is the primary route that supplies energy required for the endurance of all living things. The initial step in this process is the absorption of solar light by an organic-inorganic molecular organization called a light harvesting complex. This complicated natural solar energy conversion platform has inspired scientists to create artificial counter parts. As a means to achieve this, a self-assembled light harvesting carbon nitride/cobalt tetra-phenyl-porphyrin (CN/Co(III)TPP) material as a highly selective solar light active photocatalyst has been developed. The system exhibited excellent NADH regeneration (87.87%) and L-glutamate (94.30%) production under visible light irradiation. The current research endeavor highlights the development and application of a self-assembled CN/Co(III)TPP photocatalyst for the selective production of L-glutamate from α-ketoglutarate. [Display omitted] •A self-assembled light harvesting carbon nitride/cobalt tetra-phenyl-porphyrin (CN/Co(III)TPP) photocatalyst was synthesized•As prepared photocatalyst is characterized by several characterization techniques to determine physio-chemical properties.•Visible light active CN/Co(III)TPP photocatalyst is used for 1,4-NADH regeneration and L-glutamate production.•The yield of NADH regeneration and L-glutamate production were found to be 87.9% and 94.3%, respectively in 60 min.